2013
DOI: 10.1111/j.1365-4632.2011.05443.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of self‐reported acne in 18‐year‐old adolescent males

Abstract: Our findings showed that sensitivity and specificity of self-reported acne was very low, pointing out that, in a sample of adolescents, self-reporting of acne shows itself as an inadequate instrument for epidemiological studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 10 publications
1
11
1
Order By: Relevance
“…Regarding scar assessments, comparing self-to local professional assessments, the pilot suggests the need for dermatological assessments rather than reliance on self-assessment. As opposed to an earlier study, the pilot results hint towards a tendency of participants to minimise the presence of acne scars rather than overestimate, which was earlier found 19 . It was shown that a simple majority consensus is sufficient to determine the presence or absence of acne scars, so the use of three dermatologists is recommended for final evaluation (minimum number needed to reach a simple majority consensus).…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding scar assessments, comparing self-to local professional assessments, the pilot suggests the need for dermatological assessments rather than reliance on self-assessment. As opposed to an earlier study, the pilot results hint towards a tendency of participants to minimise the presence of acne scars rather than overestimate, which was earlier found 19 . It was shown that a simple majority consensus is sufficient to determine the presence or absence of acne scars, so the use of three dermatologists is recommended for final evaluation (minimum number needed to reach a simple majority consensus).…”
Section: Discussioncontrasting
confidence: 99%
“… 10 This may stem from a true unawareness, denial, or a reluctance to be branded as having the same disease as persons with more severe forms of acne. In a Brazilian study among male adolescents with acne, Almeida et al 19 reported that the prevalence of active acne obtained by dermatological examination was higher than that for self-reported acne, concluding that self-reporting of acne in adolescents is an inadequate instrument for epidemiological studies.…”
Section: Discussionmentioning
confidence: 99%
“…Self‐rated acne severity grading scales have been increasingly used in acne epidemiological surveys . Their advantage is that a patient‐based measure factors in the multiple dimensions of acne into a singular outcome response.…”
Section: Outcome Measuresmentioning
confidence: 99%